Forecasting of local tax realization with least square method in Tanggamus Regency - Alvindra Alvindra; Simon Sumanjoyo Hutagalung; Bambang Utoyo Sutiyoso (International Journal of Financial, Accounting, and Management, 2023)
Purpose: This study aims to identify the contribution of local taxes to regional revenues in Tanggamus Regency and predict the pattern of realization of regional tax revenues in the coming period. Research methodology: This research is a quantitative study with a time series trend analysis according to the type of regional tax and an overview of the target and its realization. The sample used in this study was data from seven types of regional taxes obtained from the Regional Financial Management Agency of Tanggamus Regency. The data analysis process uses the least squares method, often used to forecast, and the application uses Minitab software with fitted line plots and descriptive statistics features. Results: This study's results showed that the seven tax subjects seemed to go through changes and tended to grow in the future. Limitations: This research is limited to the specific scope of taxes selected and does not cover all other types of taxes and levies. Contributions: This study's ability to predict the future helps make plans for regional tax revenue, especially when it comes to planning for policies that might change in the near future. Novelty: This research is new because it has a new update on how to use predictive methods with Minitab and an analysis of how local taxes have changed over time.